Definitions matter: Multicenter investigation of incidence and outcome of poor graft function after hematopoietic cell transplantation - Konradin F. Müskens; Winny N. R. Collot‐d'Escury; Rana Dandis; Saskia Haitjema; Jürgen Kuball; Moniek A. deWitte; Marc Bierings; Caroline A. Lindemans; Stefan Nierkens; Mirjam E. Belderbos (HemaSphere)
Abstract Despite advances in allogeneic hematopoietic cell transplantation (HCT), poor graft function (PGF) remains an important complication with substantial morbidity and mortality. The investigation of preventive and therapeutic PGF treatments is hindered by inconsistencies in reported incidence and outcomes across studies, which may be explained by heterogeneity in PGF definition. To assess the impact of definition heterogeneity, we conducted a multicenter study, analyzing over 35.000 longitudinal blood counts from 427 pediatric and 405 adult HCT recipients. We compared the incidence, risk factors, and outcome of PGF, based on the three most common definitions. We identified 97 pediatric and 75 adult HCT recipients fulfilling at least one PGF definition. The 2‐year cumulative incidence of PGF varied significantly depending on the definition used, ranging from 6.8% to 20% in children and 4.9% to 18% in adults. Two‐year mortality for PGF patients ranged from 33% to 40% in children and 46% to 65% in adults. Notably, PGF patients identified solely by lenient definitions had similar mortality to HCT recipients with good graft function. Risk factors for PGF also varied by definition in both cohorts, and included older recipient age and cord blood transplantation. In conclusion, our study demonstrates that differences in PGF definition significantly impact the reported incidence, risk factors, and outcome. This underscores the need to harmonize PGF definitions across scientific studies, clinical practice, and transplant registries. Future studies, using standardized, quantitative thresholds for PGF, are required to determine optimal treatment strategies for both mild and severe forms of PGF.